Imaging findings in hypophysitis: a review - Caranci, Ferdinando; Leone, Giuseppe; Ponsiglione, Andrea; Muto, Massimo; Tortora, Fabio; Muto, Mario; Cirillo, Sossio; Brunese, Luca; Cerase, Alfonso (Radiologia medica, 2020)
Hypophysitis (HP) is a rare acute or chronic inflammatory condition of the pituitary gland. The greatest challenge in the management of HP is establishing a diagnosis through clinical criteria and non-invasive methods and predicting the patients’ clinical outcome. The aim of this review is to describe the neuroradiological findings of this rare disease, providing some information regarding the possible differential diagnosis in order to avoid unnecessary surgery. Gadolinium-enhanced pituitary magnetic resonance imaging (MRI) is considered the neuroradiological investigation of choice. The features suggestive for HP include an enlarged triangular- or dumbbell-shaped gland with a thickened and not obviously deviated stalk, further supported by the absence of posterior pituitary bright spot on T1weighted images, particularly in patients presenting with diabetes insipidus. Contrast enhancement pattern is quite variable; dural enhancement has been reported in some cases after intravenous contrast administration. The characterization of the unusual sellar mass is not straightforward and generally results in a wide differential. HP should be primarily differentiated from pituitary adenomas (including pituitary apoplexy), from pituitary metastases, and from other sellar and parasellar tumors, e.g., craniopharyngiomas, germinomas, gliomas, lymphomas, meningiomas, pituicytomas, chordomas, teratomas, dermoids and epidermoids, Rathke’s cleft cysts, and abscesses. In patients suspected for secondary forms related to systemic pathology, additional imaging is helpful in identifying other involved sites. Neuroradiologists need to know MRI appearance of this rare disease, as well as its typical symptoms and serological markers. A strict collaboration with endocrinologists and neurosurgeons is mandatory in order to reach a definitive diagnosis, allowing to promptly initiating an appropriate treatment.